2021
DOI: 10.31004/edukatif.v3i6.1279
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kohesi dan Koherensi pada Isu Nasional di Media Online Kompas.com dan Jawapos.com Edisi April 2021

Abstract: Kemudahan dalam mengakses informasi mengakibatkan sulit untuk melakukan klarifikasi atas kebenaran pemberitaan yang disampaikan. Salah satu cara yang tepat untuk menyaring informasi dengan melakukan analisis kohesi dan koherensi. Penelitian ini akan meneliti media Kompas.com dan Jawapos.com edisi April 2021 sebanyak 12 berita dengan menggunakan teori Halliday dan Hasan untuk menganalisis kohesi dan teori Kridalaksana untuk menganalisis koherensi. Metode yang digunakan adalah deskriptif kualitatif. Teknik anali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
(5 reference statements)
2
0
0
Order By: Relevance
“…In general, the results of this study confirm the results of previous studies.. Supriadi, and Mujtaba (2021) identified that the cohesion used includes grammatical cohesion, namely reference, substitution, omission, and linking. Lexical cohesion was also found, namely repetition, antonym, synonymy, hyponymy, collocation, and equivalence.…”
Section: The Opinion Rubric As Teaching Materials For Editorial Texts...supporting
confidence: 90%
See 1 more Smart Citation
“…In general, the results of this study confirm the results of previous studies.. Supriadi, and Mujtaba (2021) identified that the cohesion used includes grammatical cohesion, namely reference, substitution, omission, and linking. Lexical cohesion was also found, namely repetition, antonym, synonymy, hyponymy, collocation, and equivalence.…”
Section: The Opinion Rubric As Teaching Materials For Editorial Texts...supporting
confidence: 90%
“…Based on the results of the analysis in the opinion rubric of the Solopos newspaper, the researcher found that the most common reference data found was the single third person reference, this was indicated by the pronouns he, she, he, di-, or -nya. This has similarities with the research of Nurkholifah, Supriadi, and Mujtaba (2021) found that in this study the use of reference is very dominant because the news text in the form of a series of speeches from sources related to the issues that were informed.…”
Section: The Opinion Rubric As Teaching Materials For Editorial Texts...supporting
confidence: 81%
“…Meskipun kalimat-kalimat tersebut memiliki bentuk yang berbeda, namun mereka tetap membentuk kohesi yang kuat. Selain itu, kohesi juga mencakup keserasian hubungan dalam hal bentuk, sehingga tercipta pemahaman yang jelas dan koheren antara unsur-unsur dalam wacana tersebut (Nurkholifah et al, 2021).…”
Section: Pendahuluanunclassified
“…Penelitian dengan objek portal apresiasi online pernah dilakukan oleh (Nurkholifah, Supriadi, & Mujtaba, 2021) yaitu pada portal Kompas.com dan Jawapos.com. Penelitian yang dilakukan oleh peneliti berbeda dengan penelitian yang telah dikemukakan.…”
Section: Pendahuluanunclassified